2017
DOI: 10.1093/geronb/gbx090
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Multimorbid Medical Conditions and Health-Related Quality of Life Among Older African American Men

Abstract: These findings suggest the importance of examining clusters of comorbid medical conditions and their relationships to outcomes within older African American men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
3
10
0
Order By: Relevance
“…This is consistent with the results of a study that reported that the HR-QoL of elderly patients with MS is related to medical condition, depression, and subjective health status (Han et al, 2013;Clay et al, 2017;Yoon et al, 2016). In particular, depression showed higher odds ratios over the two classes; this is consistent with the result showing that one of the significant predictors of QoL is depression (Han et al, 2013) and that depression is associated with worsening QoL (Saboya et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the results of a study that reported that the HR-QoL of elderly patients with MS is related to medical condition, depression, and subjective health status (Han et al, 2013;Clay et al, 2017;Yoon et al, 2016). In particular, depression showed higher odds ratios over the two classes; this is consistent with the result showing that one of the significant predictors of QoL is depression (Han et al, 2013) and that depression is associated with worsening QoL (Saboya et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Many cross‐sectional studies have shown that health‐related quality of life (QOL) is reduced in multimorbidity . In a 2‐year longitudinal study of people aged >60 years, multimorbidity (two or more chronic diseases) was shown to reduce general health, body function, self‐care ability, emotion and social adaptability domains of health‐related QOL, but not memory function (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, there has been increasing interest in understanding demographic, behavioral, and social factors that shape HRQoL across various populations [5,6,7]. There is also a particular interest in understanding the factors that can explain decline and those that can be used to enhance HRQoL of aging populations, particularly in demographic and social groups in which HRQoL is low [8,9,10,11,12,13]. Given the consistent disparities across multiple domains of health, African Americans (AAs) report worse HRQoL than Whites [14,15,16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%